Mouse for Computer Control from the Joystick of the Wheelchair - Roberto Casas (Journal of Accessibility and Design for All, 2012)
Becoming autonomous is one of the biggest challenges for many people with disabilities. Increasing their autonomy usually involves the use of a wheelchair and any kind of digital assistant, such as a computer or a tablet, to communicate, to work or even for leisure. In such a situation, those people are obliged to use two different human interfaces to move a pointer and to drive the wheelchair. A joystick is the most common option to control a wheelchair. On the other hand, there are many different adapted interfaces to emulate the use of a mouse. This paper presents a system, BJoy Ring mouse, which captures the motion of the joystick on a wheelchair. The captured signal is used to move the cursor or the pointer of any digital device including an USB port. This system avoids any mechanical or electronic change in the joystick to keep its original safety and warranty. Communication between the device and the computer (or any other digital assistant) uses the USB protocol, although it could be easily improved to a Bluetooth wireless connection. Validation tests with real users proved this system to be useful aid for people with motor disabilities.